Orthogonal Latin square theory based group and batch verification for digital signatures - Hong WANG; Chengzhe LAI; Xiangyang LIU; Han ZENG (Tongxin xuebao)
In order to solve the problem of fast security verification of massive and time-intensive messages on a central node in situational awareness networks, orthogonal Latin square theory based scheme was considered.Considering efficiency promotion of security verification of messages, group design of digital signatures based on orthogonal Latin square theory was formulated, batch verification of digital signatures was processed by aggregate signature, then an efficient, parallel and non-adaptive batch verification scheme of digital signatures was proposed in according with multiple processors.Theoretical analysis and simulation results demonstrate that it will be able to identify n digital signatures by approximately <msqrt> n </msqrt> times given the upper bound d ( d≪n) of invalid digital signatures, together with higher time-efficiency and stronger error-tolerance by comparing with individual testing and binary splitting algorithms especially when multiple processors are available.